Tuberculosis-like infectious spondylitis in a cervical vertebra of a plesiosaur from the Upper Cretaceous of Patagonia, Argentina - Talevi, Marianella (2021)
Fil: Talevi, Marianella. Universidad Nacional de Río Negro, Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.